Simulation and Optimizationof aMetallic Ferry under MLC70Loading. Issue 1 (December 2020) - Lotfy, Mohamed N.; Khalifa, Yasser A.; Dessouki, Abdelrahim k.; Fathallah, Elsayed
Abstract: Floating ferries are used for both civilian and military purposes. This study concerned with a ferry composed of sixteen connected floating pontoons. This ferry is simulated and optimized to carry Military Load Capacity MLC70 (Tank load). Consequently to the increasing demand of evolution and cost optimization, the design optimization is performed in this paper to obtain the optimum minimum weight which minimizesboth the cost and the buoyancy factor. The simulation of the ferry is performed using the finite element program ANSYSsoftware. Furthermore, different grades of the structural steel, hybrid materials (steel stiffeners covered with aluminium plates) and aluminium alloy are incorporated in this study. Thesimulation is verified with both practical and mathematical results. The performance of the ferry is investigated. In addition to the design parameters, constraints and objective functions are determined. The optimum weight of the ferry is obtained, followed by a reduction in the buoyancy factor; accordinglythe capacity of the ferry can be increased. Comparison between the behaviour of the different ferries using different materials is operated considering stresses, deformations and weight. Conclusions and recommendations are then stated.